2008
DOI: 10.1093/eurpub/ckn108
|View full text |Cite
|
Sign up to set email alerts
|

Disparities between persons with and without disabilities in their participation rates in mass screening

Abstract: Although the prevalence rates of chronic diseases are higher among persons with disabilities, various types of impairments such as limb, brain, visual and internal organ impairment, hinder participation in mass screening programs for chronic diseases. The reasons for this disparity must be investigated and health policies must be altered to make preventative treatments more accessible to persons with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
20
2
Order By: Relevance
“…Unlike studies in Western countries [9,[15][16][17], the current study found no association between disability and short-term all-cause mortality among cancer patients. In South Korea, under the universal national health insurance systems, almost all members of the population have been eligible for medical security (medical insurance and medical aid) since 1991.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike studies in Western countries [9,[15][16][17], the current study found no association between disability and short-term all-cause mortality among cancer patients. In South Korea, under the universal national health insurance systems, almost all members of the population have been eligible for medical security (medical insurance and medical aid) since 1991.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies have highlighted [16,[28][29][30][31]. A worse outcome in cancer patients with visual, auditory, and linguistic impairments may be explained by the attendant communication disability, which might prevent them from seeking adequate care [32] and present another barrier to patient-physician communication [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our findings, there is a need for either private or public vision care based on age. Previous studies indicate that disability is a risk factor for multiple diseases [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…19e24 Unlike the countries described above, only a limited number of studies exist in Korea on health care utilization by people with disabilities. Studies have identified differences between people with and without disabilities using their respective probabilities of participating in health screenings 25 and rates of outpatient or inpatient care utilization. 26 However, the existing studies were cross-sectional, did not focus on people with physical disabilities, and did not include information on individual socioeconomic status or the extent of health care utilizations.…”
mentioning
confidence: 99%